1964
DOI: 10.1139/m64-025
|View full text |Cite
|
Sign up to set email alerts
|

The Microbial Metabolism of Cinnamic Acid

Abstract: A strain of Pseudomanas isolated from soil with cinnamic acid as a sole carbon source was found to be simultaneously adapted to the utilization of cinnamic acid and phenylpropionic acid. During growth on either of these compounds, o-hydroxyphenylpropionic acid and 2,3-dihydroxyphenylpropionic acid were produced in the culture medium. The organism, when grown on either cinnamic acid or phenylpropionic acid, was adapted to the utilization of m-hydroxyphenylpropionic acid and 2,3-dihydroxyphenylpropionic acid, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

1965
1965
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 12 publications
4
33
0
Order By: Relevance
“…For example, a Pseudomonas sp. reduces cinnamic acid (3-phenylpropenoic acid) to 3-phenylpropionic acid (Blakley and Simpson 1964).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a Pseudomonas sp. reduces cinnamic acid (3-phenylpropenoic acid) to 3-phenylpropionic acid (Blakley and Simpson 1964).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that many kinds of root exudates and decaying residues are phytotoxic as the result of allelochemicals contained in root exudates and decaying residues that have been isolated and identified as organic acids, especially phenolic acids, such as cinnamic, vanillic, coumaric, and ferulic (Lee et al 2006;Ohno et al 2001;Asao et al 2003). Phenolic acids frequently occurring in plants, such as ferulic, p-coumaric and syringic acids, are released during the aerobic catabolism of lignin (Kuwahara 1980;Blackley and Simpson 1964).…”
Section: Abbreviationsmentioning
confidence: 99%
“…Chemicals. propionate (DHPP) were synthesized by the procedures described by Blakley & Simpson (1964) and Burlingame & Chapman (1983). Other chemicals were purchased from Tokyo Kasei or Sigma.…”
Section: Methodsmentioning
confidence: 99%